DA CITAÇÃO COMO TRADUÇÃO E CRÍTICA NA OBRA DE MACHADO DE ASSIS - Cunha, Eliane Fernanda (Organon, 2004)
Analysis of the use of citations (both translated and not) as a criticism, was an integral part of theintellectual and literary formation of the writer-translator Machado de Assis. The translation of fragments of foreigntexts demonstrates the important role exercised by the translator’s task, not only in Machado’s literary career, butalso reveals the cultural context of 19th century Brazilian society. Translation within a comparative frameworkcontributed to the flowering of a sense of self and other and served as a fundamental piece of the translated/intertextualMachadian mosaic.